Control measures in the accounting of intangible assets of public sector entities - Kanapickienė, Rasa (Buhalterinės apskaitos teorija ir praktika, 2014)
Effective internal control helps to guarantee performance policy in an organization, achievement of the set aims; it also reveals the prospects of development, helps to indicate and manage risk so that the risk tolerance limit is maintained. One of the goals of internal control system is to ensure the reliability and sufficiency of information and financial statements. Accounting regulations set a great variety of control measures that must be guaranteed by the accounting policy adopted in a public sector entity. Yet governmental audit designates that a great share of distortions in financial statements are related with assets accounting. The object of the research is internal control measures in the accounting of intangible assets of public sector entities. The aim of the research is to investigate the regulation of internal control measures by creating the accounting policy of intangible assets of public sector entities. The article analyses and systematizes internal control measures determined in the methodological aspect of accounting policy of intangible assets of a public sector entity.
Keywords: internal control; accounting policy; public sector entity; intangible assets